Fibrillar glomerulonephritis in a patient with systemic lupus erythematosus with no evidence of lupus nephritis. Issue 2 (21st February 2023) - Whelband, Matthew Carl; Willingham, Tom; Thirunavukkarasu, Sathiamalar; Patrick, Jean
Abstract : Fibrillar glomerulonephritis (FGN) is a rare proliferative form of glomerular disease characterised by randomly oriented fibrillar deposits with a mean diameter of 20 nm. It has a rare association with systemic lupus erythematosus (SLE). We report the case of a female in her mid-50's with a 20 year history of SLE, who developed proteinuria due to FGN and had no histological evidence of lupus nephritis. She was maintained on azathioprine and prednisolone. A renal biopsy revealed randomly arranged fibrillar deposits that positively stained for DNAJB9, consistent with a diagnosis of FGN. Azathioprine was switched to mycophenolate mofetil, and the patient showed significant improvement in proteinuria. This case-based review describes the diagnosis, management and clinical outcome of FGN in association with SLE in the absence of lupus nephritis.